Effects of chlorantraniliprole on the life history traits of fall armyworm Spodoptera frugiperda (Lepidoptera: Noctuidae) - Hasnain, Ali; Zhang, Shuirong; Chen, Qinghua; Xia, Lijuan; Wu, Yutong; Gong, Changwei; Liu, Xuemei; Jian, Pu; Zhang, Lei; Wang, Xuegui (Frontiers in Physiology, 2023)
Spodoptera frugiperda is an important nomadic agriculture pest with a diverse host range and resistance against several insecticides. The current study investigated the life history traits for two strains of the field-collected population against chlorantraniliprole using an age-stage two-sex life table. For this, we established the chlorantraniliprole susceptible (Crp-SUS G12), and the chlorantraniliprole reduced susceptible (Crp-RES G12) strains, derived from the 6th generation of the QJ-20 population having resistance ratio (RR) of 10.39 –fold, compared with the reported susceptible population. The results showed that the Crp-RES G12 strain attained a 4.0 -fold RR while Crp-SUS G12 had an RR of 0.85 -fold, having overlapped fiducial limits (FL) with the referred susceptible baseline. Meanwhile, the present study revealed that the development time of the susceptible strain was significantly longer than the reduced susceptible one. Similarly, the mean longevity, adult pre-oviposition period (APOP), and total pre-oviposition period (TPOP) of females from Crp-SUS G12 were considerably longer than Crp-RES G12. Contrarily, the population parameters, including the intrinsic rate of increase (r), finite rate of increase (λ), and net reproductive rate (R) of Crp-SUS G12 were considerably lower than Crp-RES G12, while the mean generation time (T) of the Crp-SUS G12 strain was substantially longer than the Crp-RES G12 strain. The age-stage characteristic survival rate (sxj) and age-stage characteristic life expectancy (exj) of Crp-SUS G12 were longer than Crp-RES G12, but the age-stage specific reproductive value (vxj) of Crp-SUS G12 was shorter than Crp-RES G12. Moreover, the contents of Vg and VgR in Crp-RES G12 were higher than in Crp-SUS G12. These findings showed that reducing susceptibility to chlorantraniliprole promoted population growth in S. frugiperda. Therefore, this study could provide conceptual support for Integrated Pest Management (IPM) approach to control S. frugiperda in the field.